Student-athletes' attitude formation towards sport or other psychology services - Wilmot, Gregory Thomas Charlton (Rhodes University, Faculty of Humanities, Department of Psychology, 2009)
This qualitative study aims to explore attitude formation within a small sample of Tertiary level student-athletes in relation to their antecedent experiences, individual knowledge about psychology and the social factors impacting on their attitude formation. The study is intended to allow for the development of themes related to the participants' personal responses to the questions posed to them. The participants' answers from the interviews will allow for an in-depth analysis and interpretation of the constituents influencing attitude formation towards sport psychology consultation. Primarily, the study aims to explore how attitudes towards clinical and sport psychology practitioners are constructed in this sample. Clinical psychology is used as a contrasting reference point to explore attitude formation in sport psychology. The participants' beliefs, knowledge sources and attitude toward clinical psychology are examined to understand the fundamental constituents of their attitudes and to understand how this might be related to attitude formation towards sport psychology. It is intended that exploration of the participants' knowledge sources (e.g. parents, peers, media and coaches) and additional influences on attitudes towards clinical psychology are used to provide insight into how they might shape attitude formation toward sport psychology. This is viewed as particularly important as sport psychology is an increasingly important tool in assisting the enhancement of sporting performance output. This qualitative study uses four elite student-athletes from the same sporting discipline and contextual background to allow for close linkages between the participants' responses about attitude formation to be made. The study further aims to explore and understand how similarities and differences occur between the participants' responses which will be completed through analysing and drawing parallels within themes relating to the literature or emerging separately. The Literature Review is intended to help guide the research through providing a reference source for contextualizing individual, public and socially generated beliefs and knowledge (literacy) about mental health / psychology, the constituents of attitude formation and the student-athlete's context. These factors were identified in the literature as crucial components in attitude formation and also assisted in the development of initial themes, thus guiding the research. Unfortunately, there was limited literature pertaining to attitude formation in relation to sport psychology services and thus provide justification for using clinical psychology to explore attitude formation in sport psychology. This initial exploration of attitude formation in clinical psychology was used as a 'template' for contrasting attitude formation in the sample student-athletes as an indication of attitude formation in sport psychology. The Literature Review is viewed as an integral and active component of the study that is used as a body of reference guiding the exploration and interpretation of the emergent themes. This is done through the iterative reference to past research relating to attitude formation, health beliefs, and the numerous sources of information influencing attitude formation within clinical psychology and the student-athlete context. Most importantly, the Literature Review provides a significant base of information that guides the Research Question and the particular factors that have been noted as the most significant to the research. The Literature Review is intended to guide the Research Question and highlight the significant components that need to be taken into consideration in exploring attitude formation. This study, having taken the numerous individual, social, contextual and other factors into consideration, seeks to understand how such factors combine to shape attitudes and influence attitude formation. The collection of literature on social, knowledge and antecedent factors are significant in their role of shaping attitude formation and thus have been included within the Research Question. Furthermore, the Research Question and Literature Review had an impact on the Methodology and why Thematic Analysis was selected. Given the similarities in the participants' sporting and contextual backgrounds (e.g., being in the same crew, university and social context), it was felt that the primary determinants of attitude formation, within antecedent experiences, knowledge and social influences, would emerge in related themes and thus provide greater insight into attitude formation within the student-athlete context. A limiting factor however, does lie in the small number of participants from a limited diversity of backgrounds, experiences or factors that could assist in allowing broader generalisations of the findings. However, this study aims to understand how the particular factors influence or shape attitudes towards sport and other psychology services and aims to understand the more specific or 'fundamental' components of attitude formation that are experienced within the student-athlete's context and environment.
Keywords: Sports -- Psychological aspects; Attitude (Psychology); Stereotypes (Social psychology); Clinical psychology; Athletes -- Counseling of; Athletes -- Attitudes